Neospora caninum is a cause of perinatal mortality in axis deer (Axis axis) - Basso, Walter Ubaldo (2014)
Neospora caninum is a worldwide distributed protozoan that may cause neuromuscular disease in dogs and reproductive failure in domestic and wild ruminants. One axis fawn (Axis axis) and four neonates from the same deer herd died at a zoo in Argentina within a four-month period. The fawn presented with dilatation of the anal sphincter at birth and incontinence, developed weakness and ataxia and died at 14 days of age. At necropsy, a mega formation of the distal large intestine was observed. Microscopically, non-suppurative encephalitis, suppurative bronchopneumonia, fibrin necrotic enteritis and degenerative changes in the liver were observed in hematoxilin and eosin-stained tissue sections, and thick-walled N. caninum-like cysts were observed in fresh brain samples. Serologic studies for N. caninum revealed an IFAT titer of 1:6400 in the fawn and 1:25, 1:400, 1:3200 and 1:6400 in the neonates. N. caninum DNA was detected in brain samples from the fawn and from one neonate by PCR, and the parasite was isolated in vitro from the fawn´ brain after passage through gerbils (Meriones unguiculatus) and gamma-interferon knock-out mice. N. caninum DNA obtained from the fawn, neonate and isolated parasites showed the same microsatellite pattern. This suggests a common infection source for both animals. The diagnosis of N. caninum infection was confirmed, suggesting its association with perinatal mortality in captive axis deer. To the best of our knowledge, this is the first report of clinical disease associated to N. caninum infection in axis deer and of isolation of the parasite from this wild ruminant species.